2020
DOI: 10.1111/ajo.13201
|View full text |Cite
|
Sign up to set email alerts
|

External validation of risk prediction model M4 in an Australian population: Rationalising the management of pregnancies of unknown location

Abstract: Background: The prediction model M4 can successfully classify pregnancy of unknown location (PUL) into a low-or high-risk group in developing ectopic pregnancy. M4 was validated in UK centres but in very few other countries outside UK. Aim: To validate the M4 model's ability to correctly classify PULs in a cohort of Australian women. Materials and Methods: A retrospective analysis of women classified with PUL, attending a Sydney-based teaching hospital between 2006 and 2018. The reference standard was the fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The model has also been validated in Australian population and the results were convincing ( 18 ); in fact, it is a valuable tool to rationalize management in cases of pregnancy of unknown location.…”
Section: Discussionmentioning
confidence: 96%
“…The model has also been validated in Australian population and the results were convincing ( 18 ); in fact, it is a valuable tool to rationalize management in cases of pregnancy of unknown location.…”
Section: Discussionmentioning
confidence: 96%
“…Previous research suggested that UK-developed models are not as predictive when applied to American populations 36 . However, studies in Sweden, Australia and Pakistan support both M4 and M6 as superior PUL triage techniques [43][44][45][46] . Although most of these publications are retrospective, the importance of proactive validation and revalidation is clear.…”
Section: Discussionmentioning
confidence: 99%